The physiological resilience of fern sporophytes and gametophytes: advances in water relations offer new insights into an old lineage - Pittermann, Jarmila; Brodersen, Craig; Watkins, James (Frontiers in Plant Science, 2013)
Ferns are some of the oldest vascular plants in existence and they are the second most diverse lineage of tracheophytes next to angiosperms. Recent efforts to understand fern success have fo-cused on the physiological capacity and stress tolerance of both the sporophyte and the gameto-phyte generations. In this review, we examine these insights through the lens of plant water rela-tions, focusing primarily on the form and function of xylem tissue in the sporophyte, as well as the tolerance to and recovery from drought and desiccation stress in both stages of the fern life cycle. The absence of secondary xylem in ferns is compensated by selection for efficient primary xylem composed of large, closely arranged tracheids with permeable pit membranes. Protection from drought-induced hydraulic failure appears to arise from a combination of pit membrane traits and the arrangement of vascular bundles. Features such as tracheid-based xylem and vari-ously sized megaphylls are shared between ferns and more derived lineages, and offer an oppor-tunity to compare convergent and divergent hydraulic strategies critical to the success of xylem-bearing plants. Fern gametophytes show a high degree of desiccation tolerance but new evidence shows that morphological attributes in the gametophytes may facilitate water retention, though little work has addressed the ecological significance of this variation. We conclude with an emergent hypothesis that selection acted on the physiology of both the sporophyte and gameto-phyte generations in a synchronous manner that is consistent with selection for drought tolerance in the epiphytic niche, and the increasingly diverse habitats of the mid to late Cenozoic.